GR_GERICHTE ZR2 2022 43 vom 27. März 2025 , Bundesgesetz über den Allgemeinen Teil des Sozialversicherungsrechts - GR Gerichte (2025)
azione creditoria | OR 394-529 Auftrag/Gesch\x27führung o. Auftrag/Bürgschaft etc.